Ultrafine Particles Monitoring in Paris: From Total Number Concentrations to Size Distributions Measurements - Grégory Abbou; Véronique Ghersi; François Gaie-Levrel; Anne Kauffmann; Mikael Reynaud; Christophe Debert; Philippe Quénel; Alexia Baudic (Aerosol and Air Quality Research)
Abstract Due to their small size and ability to penetrate deeply into the respiratory system, ultrafine particles (UFP) pose a significant health risk. Their concentrations and sources are not consistently monitored and regulated in urban areas, including Paris. This study aims at presenting an overview of UFP measurements carried out in Paris from October 2019 to December 2022 using a mobility particle size spectrometer (MPSS). An averaged particle number concentration (PNC) of 8,100 ± 4,800 # cm−3 was recorded between 8 and 100 nm on the analysis period, which was consistent with UFP concentrations usually observed in urban background conditions (< 104 # cm−3). The maximum PNC often exceeded World Health Organization (WHO) indicative values (10,000 # cm−3 and 20,000 # cm−3 daily and hourly averages respectively), thus emphasizing the need for ongoing UFP monitoring in Paris city. At the annual scale, averaged UFP concentrations were lower in 2020 (6,600 ± 3,900 # cm−3) compared to 2021 and 2022 (8,100 ± 4,600 # cm−3 and 8,700 ± 4,700 # cm−3, respectively). This variability is depending on meteorological conditions and pollutant emissions, particularly during the first COVID-19 lockdown phase. UFP cycles can be attributed to anthropogenic emissions, mainly from road-traffic, with hourly maximum concentrations correlated with black carbon (BC, r = 0.50 with p ≤ 0.05). A correlation analysis with other pollutants also allowed to confirm road-traffic as a major UFP source in Paris due to high UFP associations with nitrogen dioxide (NO2, r = 0.58 with p ≤ 0.05) and organic matter (OM, r = 0.53 with p ≤ 0.05). Concerning particle number size distribution (PNSD) measurements, a predominant particle mode between 20 and 30 nm (Aitken mode) was observed and linked to vehicular emissions. Finally, this study is worthwhile to support policymakers and to supply future epidemiological studies to better assess UFP health impacts with the ultimate aim of defining regulation thresholds.